PEMANFAATAN POTENSI PEPAYA SEBAGAI UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DESA TAMBAK KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - Selly Astriana; IF Nurcahyo (Jurnal Kewirausahaan dan Bisnis, 2017)
Tambak Village is one of the villages in Mojosongo Subdistrict which has various natural potentials, one of them is papaya cultivation. Although supported by abundant agricultural products, but the community has not been able to optimise the potential of the region owned. The farmers have not been able to respond the market opportunities and make some innovation of the production and marketing of agricultural products. It is caused by the limited appropriate technology, the lack of investment and the limited access if the farmers to information. Therefore it is necessary to increase the farmer’s access to information, support the development of innovation of papaya cultivation, and effort to empower the farmers through a training. This public service activity is a follow-up if the programme of the thematic Real Work Course of Sebelas Maret University in 2014 in Tambak Village, Mojosongo, Boyolali. The IbM team provided technological assistance (scissors machine and cup sealer machine), training for knowledge and skills enhancement in business management of papaya chips production, increasing the supply of the raw materials with the Village Headman of Tambak ( Partner 2 ), expansion of market network, and sustainable assistance ( monitoring, advocacy, education, information ). In carrying out the main activities, the public service team cooperates with the Women Farmer Group “Delima” and the government of Tambak Village. Through the programme, the farmers are able to increase the economic value of papaya, so that ultimately they can improve the welfare of the economy and increase the community skills.